Biomechanics and elite competitive swimming - Mason, B. R. (ISBS - Conference Proceedings Archive (Konstanz), 2005)
An emphasis on servicing as opposed to research in the biomechanical support of an elite swim programme results in a quicker improvement of performance. Biomechanics brings to the coach of elite athletes objectivity and quantification with advice from a biomechanical and technical perspective. One important aspect of servicing an elite swimming programme is the development of biomechanical testing systems in which the timeliness of feedback and better accuracy is of paramount importance. Competition analysis provides much relevant information to elite swimming and it also affects a large number of athletes. Once problems are disclosed through competition analysis they need to be addressed in a training environment using biomechanical systems to assist the coach. Biomechanics systems are now available to assist the coach with start, turn, relay change and free swim analysis. Other scientific areas that are being used to advance performance in swimming include active drag, computer modelling and computational fluid dynamics. The A.I.S. is developing a new technology pool which will contain most of this technology and is to be completed by February 2006.